Risk factors for postoperative thrombosis-related complications in patients undergoing malignant brain tumor resection: a retrospective cohort study - Liu, Xiaoyuan; Zhang, Xingyue; Ma, Tingting; Li, Muhan; Zhang, Liyong; Li, Shu; Zeng, Min; Kass, Ira S.; Peng, Yuming (Frontiers in Neurology, 2023)
Introduction Patients with malignant brain tumors frequently exhibit hyper-coagulation and are at a high risk of postoperative thrombosis-related complications. However, the risk factors for postoperative thrombosis-related complications remain unclear. Methods In this retrospective, observational study, we consecutively enrolled elective patients undergoing resection of malignant brain tumor from November 26, 2018, to September 30, 2021. The primary objective was to identify risk factors for a composite of three major adverse events including postoperative lower limb deep venous thrombosis, pulmonary embolism and cerebral ischemia. Results A total of 456 patients were enrolled in this study, 112 (24.6%) patients had postoperative thrombosis-related complications, 84 (18.4%) with lower limb deep venous thrombosis, 0 (0.0%) with pulmonary embolism and 42 (9.2%) with cerebral ischemia. In a multivariate model, age more than 60 years (OR: 3.98, 95% CI: 2.30-6.88, P < 0.001), preoperative abnormal APTT (OR: 2.81, 95% CI: 1.06-7.42, P = 0.037), operation duration longer than five hours (OR: 2.36, 95% CI: 1.34-4.16, P = 0.003), and admission to ICU (OR: 2.49, 95% CI: 1.21-5.12, P = 0.013) were independent risk factor of the postoperative deep vein thrombosis. Intraoperative plasma transfusion (OR: 6.85, 95% CI: 2.73-17.18, P < 0.001) was associated with significantly increased odds of deep vein thrombosis. Conclusions Patients with craniocerebral malignant tumor have a high incidence of postoperative thrombosis-related complications. Patients over 60 years old, preoperative abnormal APTT, undergoing over-5-hour surgeries, admission to ICU, and receiving intraoperative plasma infusion might increase the odds of postoperative lower limb deep venous thrombosis. Fresh frozen plasma infusion should be used more cautiously, especially in patients with high risk of thrombosis.